Diplomasi Thailand dalam Upaya Menyelesaikan Konflik Sosial dan Politik Akibat Kudeta Junta Militer di Myanmar Tahun 2021 - Ahmad Sabil; Ali Noer Zaman (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2026)
The military coup in Myanmar in February 2021 triggered a prolonged political crisis that impacted the stability of the Southeast Asian region. This study analyzes the role of Thai diplomacy in responding to and contributing to the resolution of Myanmar's social and political conflict between 2021 and 2024. Using a qualitative approach and descriptive-analytical study, this study examines Thailand's diplomatic steps both bilaterally and multilaterally, particularly within the ASEAN framework. The results show that Thailand played a significant role as a facilitator of dialogue and negotiations with the Myanmar military junta through an approach that prioritized the principles of non-intervention, soft diplomacy, and the interests of regional stability. Thailand was also active in encouraging the implementation of the ASEAN Five-Point Consensus and facilitating informal communication channels that created a space for discussion between the junta and the international community. This study concludes that geopolitical interests, border security, and economic relations influenced Thailand's diplomatic stance and strategy in addressing the Myanmar crisis.